2017
DOI: 10.3390/app7030223
|View full text |Cite
|
Sign up to set email alerts
|

Existence, Stability and Dynamics of Nonlinear Modes in a 2D PartiallyPT Symmetric Potential

Abstract: Abstract:It is known that multidimensional complex potentials obeying parity-time (P T ) symmetry may possess all real spectra and continuous families of solitons. Recently, it was shown that for multi-dimensional systems, these features can persist when the parity symmetry condition is relaxed so that the potential is invariant under reflection in only a single spatial direction. We examine the existence, stability and dynamical properties of localized modes within the cubic nonlinear Schrödinger equation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…(21) In such cases of double symmetries, there is no need for the potential to have a special form as in Eq. (18). In addition, the soliton branch that emerges from the spectrum edge possesses both symmetries whereas the bifurcating branch loses one of the symmetries although it retains the other.…”
Section: Symmetry Breaking In Two-dimensional Potentialsmentioning
confidence: 98%
See 1 more Smart Citation
“…(21) In such cases of double symmetries, there is no need for the potential to have a special form as in Eq. (18). In addition, the soliton branch that emerges from the spectrum edge possesses both symmetries whereas the bifurcating branch loses one of the symmetries although it retains the other.…”
Section: Symmetry Breaking In Two-dimensional Potentialsmentioning
confidence: 98%
“…On the one hand, work on complex, asymmetric so-called Wadati potentials has produced mono-parametric continuous families of stationary solutions [15,16]. On the other hand, the notion of partial PT -symmetry has been explored, e.g., with models that possess the symmetry in one of the directions but not in another [17,18]. In fact, in the recent work of [19,20] that motivated the present study, it was shown that to identify critical points one can localize a soliton 1 in a way such that its intensity has a vanishing total overlap with the imaginary part of the potential, assuming that the real part of the potential is proportional to the anti-derivative of the imaginary part (but without making any assumptions on the parity of either).…”
Section: Introductionmentioning
confidence: 99%
“…On the practical side of specific applications, it would be especially relevant to consider, e.g., two-dimensional problems involving vorticity in settings such as the one of [1]. Also, more recently partially PT -symmetric settings have been introduced in [17,53] where one dimension retains the symmetry and the other dimension does not. Considering the applicability of the ideas herein in such systems or in systems with complex, yet non-PT -symmetric potentials with families of solutions [33,36] would also be of interest.…”
Section: Summary and Further Directionsmentioning
confidence: 99%